Pengaruh Struktur Aktiva, Ukuran Perusahaan, Risiko Bisnis Dan Profitabilitas Terhadap Struktur Modal Pada Perusahaan Manufaktur Sub Sektor Kosmetik Dan Keperluan Rumah Yang Terdaftar Di Bursa Efek Indonesia - Fransiska, Laurensia Renita (Managament Insight: Jurnal Ilmiah Manajemen, 2025)
The purpose of this study was to analyze the effect of Asset Structure (FAR), Company Size, Business Risk and Profitability (Return On Assets/ROA) on the Capital Structure of cosmetic and household companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The sample in this study were cosmetic companies and household needs as many as 5 companies. The analytical method used in this study is panel data regression analysis using the Eviews 10 application. Hypothesis testing is the determinant coefficient, F test, and T test. The results of the analysis in this study simultaneously show that the variables of asset structure, company size, business risk and profitability significant effect on capital structure. The results of the study partially show that the asset structure has a no significant effect on the capital structure. Firm size has significant effect on capital structure. Business risk has no significant effect on capital structure, and profitability has a no significant effect on capital structure.